Tackling multimorbidity: staff perceptions of the transition from single-condition rehabilitation to a specialist-generalist model. (2nd August 2021) - Cowie, Aynsley; Good, Kathy; McKay, Janet; Holt, Jane
Abstract : Background/aims: The Healthy and Active Rehabilitation Programme is a specialist-generalist approach to targeting multimorbidity, which was developed through reconfiguring single-condition rehabilitation pathways. This project examined staff perceptions of the transition from specialist rehabilitation, to delivering this new model. Methods: A total of 18 staff from the Healthy and Active Rehabilitation Programme (eight nurses, seven exercise instructors, two physiotherapists, one occupational therapist) participated in three focus groups, generating three key themes: apprehension, confidence growth, and integrated working. Results: Despite initial apprehension around the Healthy and Active Rehabilitation Programme's impact on the existing service, the service users, and their clinical roles, staff developed confidence in the service and in their broader roles. Integrated working within the Healthy and Active Rehabilitation Programme has enhanced their awareness of the wider rehabilitation team, and provides valuable peer support. Conclusions: This project provides valuable information for single-condition rehabilitation services that are considering delivery of specialist-generalist care to help target multimorbidity.